Incidentally Detected Kaposi Sarcoma of Adrenal Gland with Anaplastic Features in an HIV Negative Patient - Zeliha Esin Celik; Murat Celik; Erdem Sen; Hakan Cebeci; Ozlem Ata; Cagdas Yavas (Case Reports in Pathology)
Kaposi sarcoma (KS), a vascular tumor caused by infection with human herpesvirus 8 (HHV8), is a systemic disease that can present with cutaneous lesions with or without visceral involvement. Very few cases of KS, most of which were associated with AIDS, have been reported in the adrenal gland. Anaplastic transformation of KS is a rare clinical presentation known as an aggressive disease with local recurrence and metastatic potential. We report here a 47-year-old HIV negative male presented with extra-adrenal symptoms and had an incidentally detected anaplastic adrenal KS exhibited aggressive clinical course. To the best of our knowledge, this is the first case of anaplastic primary adrenal KS without mucocutaneous involvement but subsequently developed other side adrenal metastases in an HIV negative patient.